ISOLASI DAN IDENTIFIKASI FLAVONOID DALAM DAUN LAMUN (SYRINGODIUM ISOETIFOLIUM) - Rompas, Romario Aldi; Edy, Hosea Jaya; Yudistira, Adithya (PHARMACON, 2012)
Sea grass is a group of flowering plant, leaved, has its own roots and live in a shallow water.It usually used to capture sediment, compost, and as antioxidant. The use of sea grass onhuman needs to be conducted. Because of its potency and its component such as flavonoids, aresearch to identify kind of flavonoids in sea grass must be conducted. The aims of thisresearch are to isolate and identify flavonoids in sea grass (Syringodium isoetifolium) usingthin layer chromatography and spectrophotometer UV-Vis. Extraction was done withmaceration using ethanol 96% as solvent. Isolation was done by Thin Layer ChromatographyGF 6054, and n-butanol : acetic acid : water (BAA) (4:1:5). There are two spot after isolatewith TLC, the first is yellow spot with Rf 0,4 and second is red with Rf 0,8. Identification offlavonoids was done using spectrophotometer UV-Vis. Based on results, sea grass consist onflavonoids, suspected chalcon group.Keywords : sea grass, flavonoids, thin layer chromatography, UV-vis